Transglutaminase type 2 plays a key role in the pathogenesis of Mycobacterium tuberculosis infection. (4th December 2017) - Palucci, I.; Matic, I.; Falasca, L.; Minerva, M.; Maulucci, G.; De Spirito, M.; Petruccioli, E.; Goletti, D.; Rossin, F.; Piacentini, M.; Delogu, G.
Abstract: Background: Mycobacterium tuberculosis (MTB), the aetiological agent of tuberculosis (TB), is capable of interfering with the phagosome maturation pathway, by inhibiting phagosome–lysosome fusion and the autophagic process to ensure survival and replication in macrophages. Thus, it has been proposed that the modulation of autophagy may represent a therapeutic approach to reduce MTB viability by enhancing its clearance. Objective: The aim of this study was to investigate whether transglutaminase type 2 (TG2) is involved in the pathogenesis of MTB. Results: We have shown that either genetic or pharmacological inhibition of TG2 leads to a marked reduction in MTB replicative capacity. Infection of TG2 knockout mice demonstrated that TG2 is required for MTB intracellular survival in macrophages and host tissues. The same inhibitory effect can be reproduced in vitro using Z‐DON, a specific inhibitor of the transamidating activity of TG2. Massive cell death observed in macrophages that properly express TG2 is hampered by the absence of the enzyme and can be largely reduced by the treatment of wild‐type macrophages with the TG2 inhibitor. Our data suggest that reduced MTB replication in cells lacking TG2 is due to the impairment of LC3/autophagy homeostasis. Finally, we have shown that treatment of MTB‐infected murine and human primary macrophages with cystamine, a TG2 inhibitor already tested in clinical studies, causes a reduction in intracellular colony‐forming units in human macrophages similar to that achieved by the anti‐TB drug capreomycin. Conclusion: These results suggest that inhibition of TG2 activity is a potential novel approach for the treatment of TB.